2015
DOI: 10.5755/j01.itc.44.3.7720
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chaotic System for Secure Communication Applications

Abstract: The secure communication using synchronization between identical chaotic systems have been introduced in literature for a long time. A well-known practical application of chaotic synchronized systems is the Pecora and Carroll (P-C) secure communication method. In this paper, the P-C secure communication algorithm is applied to a novel three dimensional, autonomous chaotic attractor. Having a 45○ slope between sub-driver and sub-receiver circuits of a novel chaotic attractor clearly demonstrates that it can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…By utilizing chaos theory in communication schemes, the master presents the transmitter side and the slave presents the receiver side. Many synchronization techniques can be used in the chaotic systems, as shown in [35,36]. Here, an adaptive synchronization technique with a single uncertain parameter was used for synchronizing two identical new memristive chaotic systems.…”
Section: Adaptive Synchronizationmentioning
confidence: 99%
“…By utilizing chaos theory in communication schemes, the master presents the transmitter side and the slave presents the receiver side. Many synchronization techniques can be used in the chaotic systems, as shown in [35,36]. Here, an adaptive synchronization technique with a single uncertain parameter was used for synchronizing two identical new memristive chaotic systems.…”
Section: Adaptive Synchronizationmentioning
confidence: 99%
“…Since then, chaos has piqued the interest of several scientists and scientific communities around the world, and it has been effectively implemented in recent decades, mainly, in the field of communication channels. Chaos has played an important part in control applications such as regulating irregular behavior in devices and systems [5], communication privacy, and synchronization of same or separate systems resulting in data encryption, chaos spectrum radio, and secure communications [6]. A chaos system is a set of differential equations in which the solutions to two relatively comparable situations change dramatically at any given moment.…”
Section: Introductionmentioning
confidence: 99%
“…Chaos is nonlinear, designable modality and most complex steady‐state performance. Chaotic systems are very sensitive to initial conditions and system parameters, which make them preferred in security applications . In recent years, many of cryptosystems based on chaos have been researched.…”
Section: Introductionmentioning
confidence: 99%
“…The synchronization of chaos systems has important applications in secure communications . The famous functional application of synchronizing chaotic systems is the Pecora and Carroll (PC) . In 1990, PC showed that systems of chaotic can be synchronized by using various introductory conditions.…”
Section: Introductionmentioning
confidence: 99%